المشكل النحوي في المفاعيل حتى نهاية القرن السادس الهجري: دراسة تأصيلية - تحليلية - الحسون، مرتضى صباح صيوان; طالب، فاخر هاشم الياسري (جامعة البصرة - كلية الآداب, 2022)
تهدف هذه الدراسة إلى الكشف عن أهم المشكلات النحوية التي تكتنف موضوعة منصوبات الأسماء بدراسة تأصيلية تحليلية لهذه المشكلات، واقتصار البحث على الجوانب التي يتحقق فيها المشكل النحوي دون غيرها من القضايا النحوية التي لا لبس ولا إشكال فيها، وسيحاول الباحث قدر جهده بعد أن يستعرض تلك المشكلات أن يضع أهم الحلول التي يراها ناجعة ومناسبة لمثل هذه المشكلات، كل هذا سيكون مقتصرا على آراء النحويين حتى نهاية القرن السادس الهجري، ولا يعني هذا عدم الرجع إلى آراء النحويين والدارسين ممن أتوا بعد هذا القرن المذكور، ولكن سيكون الرجوع استئناسا بآرائهم وتوضيحا لما ألبس أمره من أقوال المتقدمين. وسنلقي الضوء في هذا البحث على أهم المشكلات النحوية التي تعترض المنصوبات في الدرس النحوي، ولم يتعرض الباحث للمنصوبات بالتبع؛ لأن أغلب قضاياها واضحة غبر ملبسة ولا مشكلة واكتفى بالحديث عن المشكلات النحوية في المنصوبات وأبرزها: (المفعول به- المفعول المطلق- المفعول لأجله- المفعول فيه- المفعول معه- الحال- التمييز- الاستثناء). This study aims to reveal the most important grammatical problems that surround the subject of accusative nouns in a fundamental analytical study of these problems. The research is limited to the aspects in which the grammatical problem is achieved without other unambiguous grammatical issues. The researcher will try his best after reviewing these problems to put the most important solutions that he deems effective and appropriate for such problems. All this will be limited to the opinions of grammarians until the end of the sixth century AH. This does not mean not to refer to the opinions of the grammarians and scholars who came after this century, but the reference will be based on their opinions of what was confused by the sayings of the forerunners. In this research, we will shed light on the most important grammatical problems that face the accusative nouns in the grammatical lesson. The researcher did not deal with all nouns, because most of them have clear issues and there is no problem with them. The researcher contented himself with talking about the grammatical problems in the accusatives, the most prominent of which are (object – cognate accusative- adverb of manner- adverbs of time and place- coordinated object- accusative nouns- exception).
Keywords: النحو العربي -- المسائل النحوية -- الأسماء المنصوبة